POLA ASUH ORANG TUA SELAMA PEMBELAJARAN DARING DIKETILENGSINGOLELO JEPARA - Sifa Nurrahmawati; Murtono; Ika Ari Pratiwi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses how the learning process of fourth-grade students inKetilengsingolelo and the forms of parenting applied by parents during online learning are enforced. The study discussed in this article was qualitative research with descriptive data analysis. The data collection techniques were carried out through observation,interviews, documentation, and note-taking. The results indicated that (1) the online learning process of fourth-grade students during the pandemic Covid-19 ran normally like before was the learning from Monday to Saturday by using the WhatsApp application. The students’ and teachers’activities in Whatsapp groups include delivering material from the teacher, giving assignments from student worksheets by making videos, and collecting assignments either in the form of answer sheet photos or submitting assignments in the form of videos. Subsequently, (2) theparenting style adopted by the parents was obtained from four parents who applied a democratic parenting style and one parent who applied an authoritative parenting style. Both provided a positive impact on students, especially during online learning. Student activities at home became more organized, students could learn to be disciplined, and students could takeresponsibility for their duties. There was no difference in the application of parents’ parenting styles during online learning. Still, the parents applied the same parenting styles as before the pandemic Covid-19 came up